Transitions in colonial and post colonial broadcasting : The Bahamas 1930-2003 - Storr, Juliette (2007)
Examines five significant periods of growth in the history and development of broadcasting in the Commonwealth of the Bahamas from its inception in 1930, to the introduction of private commercial radio broadcasting in 1993, to the challenges of the twenty-first century.